The Implementation of Teacher Leader Collaboration; Start-Up Project Leadership, Sekolah Guru Indonesia - Agung Pardini; Ervan Jaya; Asep Ihsanudin; Ade Munawar Luthfi (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
This article explored a learning cycle based on the collaboration of teacher leadership with students in solving actual problems through innovative and productive business start-ups. The purpose of this study is to describe the implementation of the Teacher Leader Collaboration; Start-up Project Leadership carried out during the pandemic. The Indonesian Teacher's School (SGI) during the pandemic has carried out a teacher-leader collaboration program to encourage teachers to innovate and collaborate. This research uses a qualitative case study approach. This research is on the SGI 2nd session teacher leader collaboration program. SGI is a training institution for teacher capacity building through the 10-teacher leadership curriculum, so researchers want to know the extent of the impact of implementing teacher-leader collaboration. The impact of implementing the Collaborative Teacher Leaders (KGP), Start-up Project Leadership (SPL) is not only for students and teachers but also for schools and parents. The impact of SPL on students; improves student creativity; motivates students; builds student character and increases student skills. The impact of DSS on teachers; develop teaching skills and teacher collaboration and develop teacher emotional intelligence. The impact of SPL on schools is that it can create a superior school culture. Finally, the impact on parents is that parents feel happy and proud to be able to collaborate with the school.